Hubungan Diabetes mellitus dengan Hasil Uji Konversi BTA Sputum setelah Pemberian Terapi Tuberkulosis Tahap Inisiasi - Pranoto, Avamira Rosita; Sutanto, Yusup Subagio; Haryati, Sri (Nexus Kedokteran Klinik, 2014)
Background: Pulmonary tuberculosis (TB) is a chronic infection of lung caused by Mycobacterium tuberculosis. Tuberculosis treatment often gets failure in result because of lack of care in co-morbid disease such as Diabetes mellitus (DM), which can disturb TB patient immunity. The objective of this study was to determine the relation of Diabetes mellitus and result of conversion test of sputum with alcohol-acid resistant bacillus after initiation phase of tuberculosis medication. Methods: This was an observational analytic survey with retrospective cohort study. Using consecutive sampling method, this study took 124 patients from RSUD Dr. Moewardi and BBKPM (Balai Besar Kesehatan Paru Masyarakat) Surakarta, who divided into 2 groups based on the DM status of newly diagnosed pulmonary TB patients. Control group consisted of 86 newly diagnosed pulmonary TB patients without DM; exposure group consisted of 38 newly diagnosed pulmonary TB patients with DM. Patients from both groups were given category-1 tuberculosis treatment during 2 months of initiation phase therapy, then the BTA conversion status of patients was observed. Data collected through the medical record and concurrent data of pulmonary TB patients. Data was analyzed by SPSS using Chi Square test. Probability (p) is < 0.05 with 95% confident interval. Results: There were 14 patients from the control group who failed to undergo conversion after 2 months of initiation phase therapy, whereas from the exposure group, there were 17 patients who got failure in result. Data analysis using Chi Square with significance level p < 0.05 was obtained p = 0.001 and Relative Risk (RR) = 0.66. Conclusions: DM seems to have a negative impact on the outcome of tuberculosis treatment. Pulmonary tuberculosis patients with DM as comorbid disease has probability 0.66 times lower than those without DM to get positive result from BTA sputum conversion test. Screening for DM and subsequent blood glucose control may improve the outcome of tuberculosis treatment. Keywords: Diabetes mellitus, tuberculosis medication, result of conversion test of sputumÂ